Large-Scale Characterization of the Soil Microbiome in Ancient Tea Plantations Using High-Throughput 16S rRNA and Internal Transcribed Spacer Amplicon Sequencing - Kui, Ling; Xiang, Guisheng; Wang, Ya; Wang, Zijun; Li, Guorong; Li, Dawei; Yan, Jing; Ye, Shuang; Wang, Chunping; Yang, Ling; Zhang, Shiyu; Zhang, Shuangyan; et al. (Frontiers in Microbiology, 2021)
A special interaction consists in the environment, soil microorganisms, and tea plants, composed the ecosystem of tea plantations. As a part from the influence of environmental factors and human management, the changes of the soil microbial community impacted on the growth, quality, and yield of tea plants. However, little is known about the composition and structure of soil bacterial and fungal communities in hundred-year-old tea plantations and the mechanisms by which they are affected. In this regard, we characterized the microbiome of tea plantation soils by considering the bacterial and fungal communities in 448 soil samples from 101 ancient tea plantations in eight counties of Lincang city, which is one of the domestication centers of tea in the world. 16S and ITS rRNA high-throughput amplicon sequencing techniques were applied in this study. The results showed that the abundance, diversity, and composition of the bacterial and fungal communities have different sensitivity with varying pH, altitude, and latitude. Among the influence from pH and altitude on soil microbial communities, it’s more sensitive in bacterial communities than fungi on the abundance and diversity to pH. The highest α-diversity of bacterial communities showed in the pH 4.50-5.00 and altitude 2,200 m group, and fungi peaked in the pH 5.00-5.50 and 900 m group. Under the influence of environment and geographies, all microbes presented similarly changing, and further correlations showed that it’s more sensitive in bacterial communities than fungal communities on the composition and structure which were impacted by latitude and altitude. In conclusion, the main occurrence of anthropogenic activities to the fungal community selection, rather than environmental or geographical factors; and the bacterial community is more selection to the living environment adaptation, rather than adaptation to human activities.